Multicampus university systems : Africa and the Kenyan experience - 581748 Munene, Ishmael I author (New York : Routledge, 2015)
"In the face of increasing social demand and cutbacks in state budgetary support, universities in African countries are now turning towards a multi-campus system strategy. As African governments have adopted neo-liberal education policies that lay premium on entrepreneurialism, profit making, privatization, and markets as drivers of university development, a reshaping of the academic work and organizational framework have taken place. However, little is known about the impact of this paradigm shift on access, quality and governance in higher education. This book fills the void in research and academic knowledge about the emerging university configurations in Africa. It analyzes the paradox surrounding the performance of multi-campus university systems, avenues of broadening university access but whose structural success may be qualitatively contested. This book offers a refreshing examination of the African multi-campus university system from both an African and global perspective. It makes use of empirical data from Kenya collected during extensive fieldwork along with substantive library and documentary resources on the rest of the continents to fortify arguments and demonstrate important conclusions. This allows for a comparative analysis of policies and strategies used in the establishment of campuses, both within and beyond national boundaries in the continent, and will be a welcome contribution to the existing repertoire on African universities. "--Provided by publisher